Science Forum 2016 Special Issue Inception Workshop - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
For each of its Science Fora, the ISPC has developed a special issue journal publication to inform CGIAR research and the field at large. This Brief highlights key messages from a Special Issue Workshop (https://cas.cgiar.org/spia/events/science-forum-2016-sf-2016-special-issue-workshop) held after Science Forum 16 (https://cas.cgiar.org/isdc/events/science-forum-2016).